Avaliação biológica de candidatos a metalofármacos associados à Zinco(II) em linhagens celulares de câncer de mama - Machado, Raiane Aparecida dos Santos (2023)
Breast cancer (BC) is the most commonly diagnosed malignancy worldwide. Despite advances in therapeutic strategies, the number of deaths still increases, associated especially with the resistance of tumor cells to the drugs used. In this context, metallopharmaceuticals have stood out, with Zinc(II) being one of the most used conjugates for chelating divalent compounds, with promising antitumor activity. The objective of the present study was to evaluate the biological activities of the compounds hydrazone, semicarbazone, thiosemicarbazone complexed with Zinc (II) in BC cells. For this, the tumor cell lines MCF7 (luminal BC), MDA-MB453 (HER2- positive BC) and MDA-MB231 (triple-negative BC) were cultivated, in addition to the non tumor MCF-10A (breast), HUVEC (umbilical vein endothelial) and HFF (fibroblast). Cytotoxicity, clonogenicity, migration, transcript quantification, chemosensitization and synergism with Vitamin D assays were conducted on MDA-MB231 cells. Complex 4 demonstrated to be less cytotoxic to non-tumor cell lines and complexation with the metal increased the cytotoxicity of the ligands, which was not observed for Complex 1, Complex 2 and Complex 3. In triple-negative BC cells, Complex 4 inhibited clonogenicity, migration and induced caspase-independent cell death, decreasing caspase 8 activity. Furthermore, Complex 4 chemosensitized these cells to treatments with Doxorubicin and Paclitaxel, so upregulation of CDH1 (E-cadherin) transcripts suggests the modulatory action of Complex 4 on epithelial mesenchymal transition mechanism. Finally, Complex 4 was synergistic with Vitamin D, with dose reduction (DRI > 1.0). It is expected to validate, through future in vivo assay, a new antitumor agent capable of sensitizing aggressive BC cells to treatment with chemotherapy, proving to be a promising strategy in cases of therapeutic failure.